Performance of the Modified Adult Spinal Deformity Frailty Index in Preoperative Risk Assessment. Issue 20 (15th October 2022) - Passias, Peter G.; Moattari, Kevin; Pierce, Katherine E.; Passfall, Lara; Krol, Oscar; Naessig, Sara; Ahmad, Waleed; Schoenfeld, Andrew J.; Ahmad, Salman; Singh, Vivek; Joujon-Roche, Rachel; Williamson, Tyler K.; et al.
Abstract : Study Design: Retrospective single-center, consecutively enrolled database of adult spinal deformity (ASD) patients. Objective: The aim of this study was to assess the performance of the mASD-FI in predicting clinical and patient-reported outcomes after ASD-corrective surgery. Summary of Background Data: The recently described modified Adult Spinal Deformity frailty index (mASD-FI) quantifies frailty of ASD patients, but the utility of this clinical prediction tool as a means of prognosticating postoperative outcomes has not been investigated. Methods: ASD patients with available mASD-FI scores and HRQL data at presentation and 2-years postop were included. Patients were stratified by mASD-FI score using published cutoffs: not frail (NF <7), frail (F, 7–12), severely frail (SF, >12). Analysis of vaiance assessed differences in patient factors across frailty groups. Linear regression assessed the relationship of mASD-FI with length of stay (LOS) and HRQLs. Multivariable logistic regression revealed how frailty category predicted odds of complications, infections and reoperation. Results: A total of 509 patients included (59 years, 79%F, 27.7 kg/m 2 ). The cohort presented with moderate baseline deformity: sagittal vertical axis (83.7 mm ± 71), PT (12.7° ± 10.8°), PI-LL (43.1° ± 21.1°). Mean preoperative mASD-FI score was 7.2, frailty category: NF (50.3%), F (34.0%), SF (15.7%). Age, BMI, and Charlson Comorbidity Index increased with frailty categories (all P < 0.001); however, fusion length ( P = 0.247) and osteotomy rate ( P = 0.731) did not. At baseline, increasing frailty was associated with inferior Oswestry Disability Index (ODI), EuroQol 5-Dimension Questionnaire (EQ-5D), SRS-22r, Pain Catastrophizing Scale, and NRS Back and Leg (all P < 0.001). Greater frailty was associated with increased LOS and reduced postoperative HRQL. Controlling for complication incidence, baseline mASD-FI predicted 2 year postop scores for year ODI (b = 0.7, 0.58–0.8, P < 0.001) SRS (b = −0.023, −0.03 to −0.02, P < 0.001), EQ-5D (b = −0.003, −0.004 to −0.002, P < 0.001). F and SF were associated with greater odds of unplanned revision surgery and complications. Conclusion: Higher preoperative mASD-FI score was associated with significantly greater complications, higher rate of unplanned reoperations and lower postoperative HRQL in this investigation. The mASD-FI provides similar prognostic utility while reducing burden for surgeons and patients.